Makna siratan dalam novel politik Melayu terpilih: Analisis berdasarkan gagasan kritikan Melayu / Ariff Mohamad - Ariff, Mohamad (2016)
This study analyzed "makna siratan" in expression based on five selected Malay political novels. Expression that contained "makna siratan" is used by novelist as a criticism to individual and society. Expression which involved "makna siratan" demonstrates the author's tactfulness in order to relate creative work with daily life in society. The interpretation of author's expression is associable with the function of literature as a reflection of the society and creativity in the narrative art. The analysis describes the meaning of author's expression from the dimensions of behavioural, event, and nature. Behavioural, event, and nature dimensions that discussed the "makna siratan" were deduced from the ten principal of Malay Criticism Construct by Dr. Syed Othman Syed Omar. Five Malay novels with political theme chosen are Sebelas Rejab, Anak Mat Lela Gila, Tunggul-tunggul Gerigis, Nagogho Astana dan Naratif Ogonshoto. All five works represent Malay literature work production time in novel genre from time before independence, independence era and after year 2000. Analysis from the five novels found that the relevancy of Malay Criticism Construct exist in the interpretation of "makna siratan" particularly in the dimensions discussed earlier, which are behavioural, event, and nature. The findings proved the appropriateness of the construct through expressions that involved "makna siratan" in Malay political novels.